Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang di Pasar Reok Kabupaten Manggarai Nusa Tenggara Timur Tahun 2020 - Jomi, Maryunus; Widodo, Sugeng; Hariani, Ermatry (Economie: Jurnal Ilmu Ekonomi, 2020)
Traditional markets are still very important centers of economic activity for some people in Indonesia. In the market, someone can distribute the products they produce for sale, with this activity the sellers can get income every day. "And this study aims to determine the four factors that affect the income of traders in Reok Market, Manggarai Regency, East Nusa Tenggara. And the variables of this study are business capital (X1), education level (X2), working hours (X3), length of business (X4), and merchant income (Y). The data analysis technique used to test the hypothesis is regression analysis with a significant level of 5%. The results of the analysis show that partially the significant variable affecting the income of Pasar Reok traders is venture capital (X1). While three other independent variables such as education level (X2), working hours (X3), and length of business (X4) partially do not have a significant effect on the income of Pasar Reok traders. For the variables of business mode, education level, working hours, and length of business simultaneously have a significant effect on the income of Pasar Reok traders”.